Generation of Cryomyces antarcticus mutants to explore the importance of DHN melanin for survival - Catanzaro, Ilaria (2023)
Cryomyces antarcticus, a cryptoendolithic melanized fungus endemic to Antarctica (phylum Ascomycota, class Dothideomycetes incertae sedis), has demonstrated high capability to survive extreme environmental conditions like those found in space (e.g., ionizing radiation, vacuum, microgravity), thus fueling fundamental astrobiological questions like “the search for life beyond Earth”. Its extraordinary resilience has been attributed to the presence of thick, highly melanized cell walls, which may contain both DHN and DOPA melanins. To better understand the contribution of DHN melanin to the overall resilience of C. antarcticus, we decided to generate melanin-deficient mutants by genetic engineering. For this, the melanin-PKS (polyketide synthase)- encoding ortholog was identified in the C. antarcticus CBS 116301 genome and used to design primers for re-sequencing of the capks1 locus in the strain CCFEE 515. Based on the genetic toolkit developed for the black fungus Knufia petricola, we designed a strategy for mutating capks1. Protoplasts of C. antarcticus CCFEE 515 were generated and co-transformed with a circular AMA-containing plasmid for expression and in-vivo assembly of Cas9 and two capks1-specific sgRNAs and a PCR-generated donor DNA i.e., a hygromycin resistance cassette flanked by ~75-bp-long sequences homologous to the capks1 locus. Transformation of C. antarcticus is challenging because of its very slow growth and uncertain gene copy number. It took six months from obtaining enough biomass for cell wall lysis to transferring the putatively resistant transformants for genotyping, but we eventually managed to generate three independent non-melanized (whitish) Δcapks1 mutants! We are now awaiting first complemented strains as ultimate genetic transformation control. They are considered to have a wild-type-like pigmentation due to the reintroduction of the wild-type capks1 into the Δcapks1 mutant.